Lost horizons: The noncooperative management of an evolutionary biological system - Timo Goeschl; Timothy M. Swanson (Fondazione Eni Enrico Mattei (FEEM), 2002)
This paper studies the interaction between two dynamic domains, (1) an evolutionary biological system ('the environment') whose behaviour determines the availability of a resource stock, and (2) an industry where access to the resource stock is determined by the outcome of a patent race. The specific setting of the model is that of managing microbial resistance to antibiotics. Here, resistance develops in response to the use of antibiotics above a threshold level. We show that the optimal policy from society's point of view is to generate through R&D a diversified portfolio of antibiotics that maintains a steady-state of resistance. In practice, however, the management of the resistance stock is left to an industry operating under a system of intellectual property rights (IPR). There, firms are involved in a sequence of patent races to supply the antibiotic with the best cost-effectiveness ratio. The paper studies the structure of the patent race within the industry against the background of pathogen evolution. We show that a multi-firm industry operating under an IPR-based incentive mechanism is unlikely to generate the socially optimal number of antibiotics because IPR systems (1) create incentives for sequential rather than simultaneous innovation; (2) generate incentives that decline with the number of previous (shelved) discoveries; and (3) generate incentives that respond perversely to increases in biological system velocity. These results highlight the importance of well-designed dynamic incentives for managing resource stock dynamics.
Keywords: Q28; I18; O34; 330; Resource Management; Intellectual Property Rights; Evolution; Resistance; Antibiotics; Bioökonomik; Pharmazeutisches Produkt; Immaterialgüterrechte; Theorie; Pharmazeutische Forschung